Blended Learning Application in Higher Education: EFL Learners’ Perceptions, Problems, and Suggestions - Agus Rianto (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2020)
This study sought to explore Indonesian university students' perceptions, problems, and suggestions of the application of blended learning in their EFL courses. A questionnaire consisting of 6 categories (benefits of online learning, benefits of face-to-face learning, learning assessment, problems in blended learning, suggestions for quality improvement of blended learning, and open-ended questions) was used as the research instrument. The collected data were analyzed descriptively and qualitatively. The results showed that most of the students perceived positively both the online and face-to-face modes used in their blended EFL courses, although they tended to have negative views on certain online technical aspects. Internet connectivity was the main problem and the solution of all technical problems was the main suggestion reported by the students. As this research was conducted only with students from one study program, the results should not be generalized and future research is suggested to be more focused on the comparison of students’ preferences for other blended course formats and relate them to students’ EFL achievement.